Peredaran Vitamin C Injeksi Ilegal di Indonesia - Dewa Gede Bayu Rastika; Neti Triwinanti; Muhammad Gafur Salaffudin (Eruditio : Indonesia Journal of Food and Drug Safety, 2022)
Vitamin C has various benefits for both health and beauty. The high demand for vitamin C, especially the injection type, raises the crime potential where some individuals distribute illegal vitamin C injections. In Indonesia, vitamin C injection is categorized as a prescription drug used to treat vitamin C deficiency, and some countries have banned the use of it as a whitening agent. Illegal vitamin C injection distribution risks public health because its safety, efficacy, and quality aren’t guaranteed. This paper aims to identify types of illegal vitamin C injections circulating in Indonesia, map the distribution of illegal vitamin C injections, including the modus operandi used, and formulate recommendations to prevent its distribution in Indonesia. This research was conducted using a qualitative method with a narrative approach as well as primary and secondary data collection. As a result, some brands of illegal vitamin C injections circulating in Indonesia are Bionic White Skin, Neutro Skin, Vitamin C + Collagen, VC Injection, and Vitamin C Daehan New Pharm. According to the laboratory test, the level of vitamin C from 3 of 4 illegal vitamin C injections doesn’t meet the requirement, indicating low product quality and a chance of product counterfeiting. Some modus operandi by criminals found are sales through e-commerce, beauty clinics, and exhibitions. Influencers also have an important role in the decision made by society to use illegal vitamin C injections. Therefore, it is recommended to strengthen supervision, including cyber patrols, raising awareness, tracing distribution facilities, and collaboration by various stakeholders to prevent the circulation of illegal vitamin C injections in Indonesia.